Influence of Puspa Wood and Coconut Trunk Combination on the Characteristics of Cross-Laminated Timber Bonded with Polyurethane Adhesive - Siti Aisyah; Yusuf Sudo Hadi; Muhammad Adly Rahandi Lubis; Muhammad Iqbal Maulana; Rita Kartika Sari; Wahyu Hidayat (Jurnal Sylva Lestari, 2023)
The purpose of this study was to evaluate the characteristic of cross-laminated timber (CLT) made from puspa (Schima wallichii) wood, coconut (Cocos nucifera) trunk, and their combination using a polyurethane (PU) adhesive. The manufacturing of CLT begins with the characterization of the adhesive and wood materials used in this study. The CLT panels are made with dimensions of 100 cm × 30 cm × 3.6 cm. The laminate was organized into three layers with the face/core/back, namely puspa wood (PPP), coconut trunk (CCC), and their combination (PCP and CPC), perpendicular to each other using polyurethane adhesive with a glue spread of 160 g.m-2. The physical and mechanical properties of the CLT were assessed according to the JAS 3079 (2019) standard. The results showed that the polyurethane adhesive used in this study could cure optimally at a temperature of 30°C for 200 minutes. Puspa wood and coconut trunk had different physical and chemical properties but had similar wettability to polyurethane adhesives. The physical and mechanical characteristics of coconut CLT were better than puspa CLT. Based on the overall test results, the puspa hybrid CLT is better than the single wood species of the CLT. In contrast to coconut hybrid CLT, the single CLT of CCC was better than its hybrid CLT. Keywords: Coconut trunk, cross-laminated timber, layer combination, polyurethane adhesive, puspa wood